PENGARUH MANAJEMEN PROYEK DAN KUALITAS PROYEK TERHADAP PENCAPAIAN TARGET PEMBANGUNAN INFRASTRUKTUR JALAN DI CV. ASWAN - Hia, Aldof Dikyanto Sonasa; Zai, Kurniawan Sarototonafo; Mendrofa, Martha Surya Dinata; Zebua, Serniati (Jurnal Suluh Pendidikan, 2025)
This study aims to analyze the influence of project management and project quality on the achievement of road infrastructure development targets at CV. Aswan, located in Togimbogi Village. The research methods used include direct observation at the project site, distributing questionnaires to respondents involved in the project, and analyzing relevant documents to support the data obtained. The questionnaire measured respondents' perceptions of project management and project quality implemented. The data collected were then analyzed using SPSS version 25 software to ensure the validity and reliability of the research instrument. The results of the analysis showed that there was a significant positive influence between project management and project quality on the achievement of road infrastructure development targets. The population in this study was all workers at CV. ASWAN, totaling 32 people. There are (Three) variables studied in this study, namely: 1) project management. 2) project quality, 3) road infrastructure development. The tool used in this study was a questionnaire. This study also identified several challenges faced in project implementation, such as delays and communication problems between teams. These findings are expected to provide valuable insights for CV. Aswan management in formulating more effective strategies in project implementation, as well as being a reference for further research in the field of project and construction management. Thus, this study contributes to the development of project management science in Indonesia